Hubungan Antara Supervisi Akademik dengan Kompetensi Pedagogik Guru - Tabitha Angelicha; Herry Sanoto (Jurnal Studi Guru dan Pembelajaran, 2021)
This research aims to determine the relationship between academic supervision and teacher pedagogical competence. The subjects of the study included 3 class teachers from Elementary School of 1 Plumbon and 3 class teachers from Elementary School of 3 Sambungmacan. This research was a quantitative study and this study used the correlation method. The data collection technique in this study used a questionnaire method where the data were analyzed, namely test instruments in the form of validity and reliability tests and hypothesis testing in the form of Spearman Rank correlation. Through the Spearman Rank correlation test, it shows good results in the form of a correlation coefficient value of 0.868, where the correlation coefficient value is included in the criteria for a very strong relationship level. This shows that there is a very strong relationship between the variable of academic supervision and the variable of teacher pedagogical competence.